If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7 = 5 + -1(2x + -9) Reorder the terms: -7 + 5x = 5 + -1(2x + -9) Reorder the terms: -7 + 5x = 5 + -1(-9 + 2x) -7 + 5x = 5 + (-9 * -1 + 2x * -1) -7 + 5x = 5 + (9 + -2x) Combine like terms: 5 + 9 = 14 -7 + 5x = 14 + -2x Solving -7 + 5x = 14 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -7 + 5x + 2x = 14 + -2x + 2x Combine like terms: 5x + 2x = 7x -7 + 7x = 14 + -2x + 2x Combine like terms: -2x + 2x = 0 -7 + 7x = 14 + 0 -7 + 7x = 14 Add '7' to each side of the equation. -7 + 7 + 7x = 14 + 7 Combine like terms: -7 + 7 = 0 0 + 7x = 14 + 7 7x = 14 + 7 Combine like terms: 14 + 7 = 21 7x = 21 Divide each side by '7'. x = 3 Simplifying x = 3
| 2(t)=-0.8t^2+24t+8 | | 9(x+8)=5(3x-6) | | 7/8/5/18 | | 8m^2+4m^2-6m^2= | | -8x+18=-6(x-4) | | 17x-4=13x+12 | | 15+7x-5=-6+8x | | x/0.35 | | b+25=80 | | 1+1=55 | | 8x-4x+(-23x)= | | 1/5x+4=10 | | Cos(2x)=.20 | | 11x/4=2x/5 | | 7x=7(6-x) | | 5x-10=4-(x-14) | | 10(x+8)=5(4x-8) | | -2.6+10.5=4.4n | | 12x+4=4(x+3) | | 15-3x-1=-x-10 | | 2x+3(3/2)=17 | | 3x+3+8x-9=7x+5 | | 2/x+8=4/x | | -4.2x+31.5=-2 | | (7y^2-2y+8)+(3y^2-3y-5)-(6y^2-6y-5)= | | 25x^2/15x | | x+11+2x-5=72 | | 1/(h+5)=1/(3(h+4)) | | y=-x+8(1)+8 | | y=2x-7(1)-7 | | g^2=9g | | 10(x+1)-5(x-2)=70 |